2020
DOI: 10.1177/1091581820932875
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Mitochondrial Regulation of Epigenetic Modifications in Association With Carcinogenic and Noncarcinogenic Polycyclic Aromatic Hydrocarbon Exposure

Abstract: Polycyclic aromatic hydrocarbons (PAHs) refer to a ubiquitous group of anthropogenic air pollutants that are generated through incomplete carbon combustion. Although the immunotoxic nature of PAHs has been previously reported, the underlying molecular mechanisms of this effect are not fully understood. In the present study, we investigated the mitochondrial-mediated epigenetic regulation of 2 PAHs, carcinogenic (benzo[a]pyrene; BaP) and noncarcinogenic (anthracene [ANT]), in peripheral lymphocytes. While ANT e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Interestingly, epigenetic modifications may remain preserved among the circulating nucleic acids aroused primarily from cell death and can be used to generate an epigenome-wide analytical landscape comprising essential insights of an individual’s disease status (Bhargava et al, 2017; Bhargava et al, 2018a). It is now evident that the exposure to different environmental pollutants, such as PM and residual organic compounds can cause epigenetic imbalances (Shukla et al, 2019; Bhargava et al, 2020). However, during such processes, the components of pollutants, which have varying extents of health impacts and toxicity, have an important role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, epigenetic modifications may remain preserved among the circulating nucleic acids aroused primarily from cell death and can be used to generate an epigenome-wide analytical landscape comprising essential insights of an individual’s disease status (Bhargava et al, 2017; Bhargava et al, 2018a). It is now evident that the exposure to different environmental pollutants, such as PM and residual organic compounds can cause epigenetic imbalances (Shukla et al, 2019; Bhargava et al, 2020). However, during such processes, the components of pollutants, which have varying extents of health impacts and toxicity, have an important role.…”
Section: Discussionmentioning
confidence: 99%
“…After PCR cycles, dCt values were obtained by subtracting Ct value of internal control to the Ct value of the test gene. ddCT values were obtained by reducing the dCt (Low-risk) from dCt (high-risk) and fold change was calculated by using formula 2 A(dclct) (Bhargava et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Whereas, mixture of heavy metals and PAH decreased telomere length and increase DNA methylation [253] . In addition, post translational modification of Histone such as methylation, acetylation and phosphorylation after exposure to PAH triggers chromatin structure modulation [220] , [254] , [118] , [255] , and also induced methylation of mitochondria DNA [256] . Various effects of PAH on histone and DNA methylation as reported included suppression of Histone methyltransferase Dot 1-like protein [257] , Long Interspersed Element-1 (LINE-1), and O6 methylguanine-DNA methyltransferase (MGMT) [258] .…”
Section: Search String and Databasesmentioning
confidence: 99%
“…Several studies have proposed additional methylated genes as biomarkers of benzo[a]pyrene-associated cancer [68,69] with changes to the global methylome being associated with the development and progression of cancer [68,70]. Benzo[a]pyrene exposure in human lymphocytes induced aberrant expression of DNMT1 and hypomethylation of nuclear and mitochondrial DNA, initiating histone methylation and modifying chromatin structure; this cascade of epigenetic events may provide insight into the mechanisms of benzo[a]pyrene associated toxicity [71].…”
Section: Dna Methylationmentioning
confidence: 99%
“…The influence of benzo[a]pyrene-induced inflammation was further explored within human adenocarcinoma mammary cells cotreated with benzo[a]pyrene and a pro-inflammatory cytokine IL-6[77]; genotoxicity was enhanced due to the downregulation of miRNA-27b, allowing increased CYP1B1 metabolism of benzo[a]pyrene to reactive intermediates. Several studies have shown in vitro benzo[a]pyrene exposure caused prominent changes in the expression of miRNAs and their respective target genes, providing mechanistic insight into benzo[a]pyreneassociated toxicity[71,78].In addition to the focus on miRNA, recent studies investigated the role of lncRNA in mediating benzo[a]pyrene-associated effects. For example, the significant upregulation of linc00673 following benzo[a]pyrene exposure within human non-small cell lung cancer cells (A549) increased cell migration, invasion, and epithelialmesenchymal transition[79].…”
mentioning
confidence: 99%